Seroprevalence of SARS‐CoV‐2 infection among pet animals in Croatia and potential public health impact - Stevanovic, Vladimir (Transbound Emerg Dis, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged in late 2019 and has since caused a global pandemic. Experimental studies and sporadic reports have confirmed susceptibility of dogs and cats to SARS‐CoV‐2 infection. However, the importance of pet animals in the epidemiology of this infection is unclear. This study reports on a first large‐scale serosurvey of SARS‐CoV‐2 infections in dogs and cats in Europe. From 26 February 2020, just one day after the first confirmed human case of SARS‐CoV‐2 infection in Croatia, to 15 June 2020, dog and cat serum samples were collected from animals admitted to three veterinary facilities in Croatia. Additionally, on 25 May 2020, a total of 122 serum samples from employees of the Faculty of Veterinary Medicine University of Zagreb were collected. Total of 656 dogs and 131 cat serum samples were tested using an in‐house microneutralisation test (MNT). Human serum samples, as well as 172 randomly selected, dog sera were tested using enzyme‐linked immunosorbent assay (ELISA). ELISA‐positive human sera were subsequently tested using MNT. Neutralising antibodies were confirmed in 0.76% cats and 0.31% dogs. ELISA reactivity was recorded in 7.56% tested dog sera. On the other hand, 5.19% of administrative, basic and pre‐clinical sciences department personnel and 5.13% of animal health service providers and laboratory personnel tested ELISA positive. Neutralising antibodies were not confirmed in any of the human samples. In conclusion, seropositivity among pet animals in Croatia is low, especially when compared to results from China. A small number of seropositive animals with a low titre of neutralising antibodies suggest infections are rare and are following infections in the human population. Additionally, contact with animals does not seem to be an occupational risk for veterinary practitioners.